2022
DOI: 10.3390/ijms23084339
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Nanoparticles and Intestine

Abstract: The use of nanoparticles (NPs) has surely grown in recent years due to their versatility, with a spectrum of applications that range from nanomedicine to the food industry. Recent research focuses on the development of NPs for the oral administration route rather than the intravenous one, placing the interactions between NPs and the intestine at the centre of the attention. This allows the NPs functionalization to exploit the different characteristics of the digestive tract, such as the different pH, the intes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 226 publications
0
29
0
Order By: Relevance
“…43 In addition to their use as drug carriers, some metallic nanoparticles have also shown potent antimicrobial properties (e.g., silver nanoparticles) and immunogenicity, which can be explored further for therapeutic applications. 44 Extracellular vesicles (EVs) are nanosized vesicles that are naturally released from cells. EVs are responsible for facilitating intercellular communication by transporting different macromolecules such as miRNA and proteins throughout the body.…”
Section: Nanoparticles In a Nutshellmentioning
confidence: 99%
See 2 more Smart Citations
“…43 In addition to their use as drug carriers, some metallic nanoparticles have also shown potent antimicrobial properties (e.g., silver nanoparticles) and immunogenicity, which can be explored further for therapeutic applications. 44 Extracellular vesicles (EVs) are nanosized vesicles that are naturally released from cells. EVs are responsible for facilitating intercellular communication by transporting different macromolecules such as miRNA and proteins throughout the body.…”
Section: Nanoparticles In a Nutshellmentioning
confidence: 99%
“…The human GI tract consists of mucus, a variety of epithelial cells, immune cells, and blood and lymphatic vasculature, all with specialized functions. 3 Additionally, unlike systemic administration, oral drug delivery exposes therapeutics to first-pass hepatic metabolism that can significantly reduce the drug bioavailability prior to reaching systemic circulation. The development of drug delivery methods based on nanomaterials has made it possible to overcome some of these barriers, for example, by shielding drugs from digestion in the harsh intestinal environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous review has summarized the toxicity mechanism of nanoparticles, including oxidative stress, inflammatory response, and DNA damage in systemic (animal) and cellular studies [ 25 ]. We and others have also found that ENMs may induce versatile immune responses in the process of antigen recognition and uptake, as well as in the developed innate and adaptive immune responses in the gut [ 26 , 27 ] and skin [ 28 , 29 ]. In the present study, we explored whether similar biological effects and mechanisms are developed after exposure to nZnO and nAg in the airways.…”
Section: Discussionmentioning
confidence: 99%
“…117–119 Moreover, unlike polymeric or lipid NPs, metallic NPs tend to have great stability under interstitial fluid pressure. 120,121 In addition, metallic NPs present a high surface-to-volume rate, which can be easily modified and efficiently loaded with drug agents. 122,123 Therefore, metallic NPs are currently utilized in various fields including diagnostic, therapeutic, and drug delivery potential.…”
Section: Np Systemsmentioning
confidence: 99%